Hepatitis C: Crioglobulinemia y vasculitis cutánea con acronecrosis. Reporte de un caso. - MOSTORINO ELGUERA, Rosa (2013)
The C Hepatitis, it is a RNA virus of the Flaviviridae family, that introduces within their spectra of infection, manifestations liverworts and extrahepatic, being these last few frequent. Crioglobulinas could be detected in a third of patient with C hepatitis, but in only 1-2% of the cases develop cutaneous manifestations, some of this manifestatios are vaculitis with acronecrosis. The infection for C hepatitis occurs in other countries with diferent prevalence, they have more prevalence than in our countrie, being different to the prevalence for other types of viral hepatitis (B hepatitis). We are introduced the case of a patient attended to in our department with infection for C hepatitis and extrahepatic manifestations(acronecrosis) associate to presence of crioglobulinas.